1987
DOI: 10.1557/proc-112-61
|View full text |Cite
|
Sign up to set email alerts
|

Slag-Based Saltstone Formulations

Abstract: Approximately 400 × 106 liters of low-level alkaline salt solution will be treated at the Savannah River Plant (SRP) Defense Waste Processing Facility (DWPF) prior to disposal in concrete vaults at SRP. Treatment involves removal of Ca+and Sr+2 followed by solidification and stabilization of potential contaminants in saltstone, a hydrated ceramic waste form.Chromium, technetium, and nitrate releases from saltstone can be significantly reduced by substituting hydraulic blast furnace slag for portland cement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…What we observe from Serne et al (1992) Langton (1988) reported low (slow) D e values using SRS saltstone (10 -12 cm 2 /s). In Serne et al (1992), the Tc(VII) was added to two cement formulations (T106-AN 47.5% slag and DSSF 47% slag).…”
Section: Tc Leaching Studies For Cementitious Waste Formsmentioning
confidence: 41%
See 4 more Smart Citations
“…What we observe from Serne et al (1992) Langton (1988) reported low (slow) D e values using SRS saltstone (10 -12 cm 2 /s). In Serne et al (1992), the Tc(VII) was added to two cement formulations (T106-AN 47.5% slag and DSSF 47% slag).…”
Section: Tc Leaching Studies For Cementitious Waste Formsmentioning
confidence: 41%
“…Brodda (1988) and Tallent et al (1988) also did D e measurements of slag-cements and reported that nitrate (indicative of a conservative tracer or of how fast water moves) leached about 100 times faster than Tc. Langton (1988) , respectively. The NO 3 -D e values for the 0%, 15% and 26% slag concentrations were 10 -9 , 10 -7 and 10 -9 , respectively.…”
Section: Tc Leaching Studies For Cementitious Waste Formsmentioning
confidence: 97%
See 3 more Smart Citations